Color Reflectance (Spectrophotometer) of IODP Hole 389-M0096F - Jody M Webster; Ana Christina Ravelo; Hannah Grant; Margaret S Stewart; Marisa Rydzy; Erwan Le Ber; Nicola Allison; Ryuji Asami; Brian Boston; Juan-Carlos Braga; Logan Brenner; Xuefei Chen; et al. (PANGAEA, 2025)
Color reflectance spectrophotometry and colorimetry data from the above given hole of International Ocean Discovery Program (IODP) Expedition 389 (Hawaiian Drowned Reefs). The data where obtained during the onshore phase of expedition 389 which took place between 2025-02-06 to 2025-02-26 at the Bremen Core Repository (BCR) hosted at MARUM – Center for Marine Environmental Sciences, University of Bremen. After longitudinal splitting of the core sections, each archive half was scanned by a handheld Konica Minolta spectrophotometer (Model CM-2600d), recording data at approximately 2-cm sampling interval. Interval spacing was adjusted appropriately depending on the nature of the core (i.e., the presence of rubble, vugs, and fractures) and commented on in the data report. Measurements were taken in the most visibly homogeneous areas at each depth downcore to obtain as pure a color reflectance signal as possible. The obtained data is represented in the L*a*b* color coordinate system, where L* is a total reflectance index ranging 0%–100%, a* is green (<0) to red (>0) chromaticity, and b* is blue (<0) to yellow (>0) chromaticity. Furthermore, the analyses give Munsell color values , and intensity values for 31 contiguous 10 nm wide bands across the 360–740 nm interval of the light spectrum with a reflectance range of 0%–175% and a resolution of 0.01%. For further methodological information see methods chapter in0.167emWebster, J.M. et al., 2025 https://doi.org/10.14379/iodp.proc.389.2025